Testing a biological active plant extract’s antifungal effect against soil fungi - Tóth, Csaba Tamás; Szabó, Zsuzsanna; Csubák, Mária (Acta Agraria Debreceniensis, 2012)
In Hungary today is about 5 million hectares of agricultural land contaminated with ragweed. The ragweed problem a year is about 60 billion HUF to be paid, of which 30 billion are used to reduce the agricultural damage. Experiments with ragweed pollen has mainly been carried out in connection with terms of allergy. The other biochemical experiments and studies with this plant, have so far been the scientific horizons of public life, boosted the edge. We wanted to demonstrate that the ragweed, which is a weed, containsbiological active (for example: antifungal) compounds. For our experiments in the previous cycle of flowering, plants were collected manually, with its roots and with each plant part. The extraction of the substance from dry plant – meal was carried out using appropriate solvents. The biological activity of ragweed-extracts were tested against fungi isolated from soils and meadow with different mode of cultivation. Our results suggest that ragweed contains biologically active substances, which inhibit the growth of fungi, depending on the concentration of active ingredients of the plant.